Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Injibara University - International Livestock Research Institute; Injibara University (2021)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and Injibara University. MOU signed on December 23, 2021, by Jimmy Smith, Director-General of ILRI and Aemero Tadesse, President of Injibara University.